2012
DOI: 10.1002/anie.201202750
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metals in Polyoxometalates

Abstract: Polyoxometalates containing noble metal ions, such as ruthenium, osmium, rhodium, palladium, platinum, silver and gold, are a structurally diverse class of compounds. They include both classical heteropolyanions (vanadates, molybdates, tungstates) in which noble metals are present as heteroatoms, as well as the recently discovered class of polyoxometalates with noble metal "addenda" atoms. The focus of this Review is on complexes that should, in principle, exist as discrete molecular species in solution, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
185
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 367 publications
(191 citation statements)
references
References 232 publications
1
185
0
2
Order By: Relevance
“…Polyoxometalates (POMs) are discrete metal oxide clusters that are of current interest as soluble metal oxides, as well as for their application in catalysis, medicine, and materials science [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recently, open-Wells-Dawson POMs have been reported as an emerging class of POMs [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are discrete metal oxide clusters that are of current interest as soluble metal oxides, as well as for their application in catalysis, medicine, and materials science [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recently, open-Wells-Dawson POMs have been reported as an emerging class of POMs [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental requirements for a transition metal to serve as addenda are the ability to adopt a variety of coordination modes (mainly 4 to 6) in response to acidification, have high positive charge, and are capable of pπ-dπ interactions. However, there are a few examples that deviate from this set of rules, as reported by Kortz et al, where the authors demonstrated the preparation and characterization of metal oxides made of noble metals such as Au [16,17] and Pd [18][19][20][21][22] in the presence of supporting organic or inorganic ligands.…”
Section: Pom-based Clusters and Supramolecular Aggregatesmentioning
confidence: 99%
“…Polyoxometalates (POMs) are discrete metal oxide clusters that are of interest as soluble metal oxides, with applications in catalysis, medicine, and materials science [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recently, the open-Wells-Dawson POMs have been an emerging class of POMs [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] [29].…”
Section: Introductionmentioning
confidence: 99%